Description of the geographic distribution of excessive drinking across regional cultures in the United States: Framing an important health metric according to the cultural context of the American nations - Shane A. Phillips; Ross Arena; Nicolaas P. Pronk; Colin Woodard (PLoS ONE, 2026)
Excessive alcohol drinking results in an increased risk for chronic diseases, and the rates of alcohol consumption have increased among U.S. adults in the past decade. The U.S. Surgeon General called for updating consumer labels to include this risk. This paper aims to understand the regional distribution of excessive drinking and how these patterns may be explained according to the American Nations model of the first U.S. settlement streams. We present data from the 2024 County Health Rankings program to demonstrate the distribution of excessive drinking, showing that excessive alcohol drinking patterns are region-specific and predicted by the American Nations model. This paper introduces the American Nations model in promoting alcohol consumption reduction messages.